Reviewing and Analyzing the Famous Opinion and the Civil Law about Fudhuli (Unauthorized) Sale Based on the Maxim “Contracts Follow Intentions” - Zeinab Sanchouli; Muhammad Reza Kaykha (آموزه‌‌های فقه مدني)
Fudhuli (unauthorized) sale has been formed in two types: sale for himself (thief and usurper) and for the owner. The civil law with following the well-known Islamic jurists, the mentioned sale is valid (legal) but it is not effective that its obligation and validity depends on the consent of the real owner. Among this, some Islamic jurists in contrast to the famous opinion believe the voidance of fudhuli (unauthorized) sale. The findings of this note which has been adopted in the descriptive-analytic method reveal that the well-known opinion and the civil code with paying attention to the maxim “contracts follow intentions” is debatable and also the opinion of Kashif-al-Qita who believes the validity of the sale for the unauthorized dealer and the opinion of the voidance of the fudhuli (unauthorized) sale totally is arguable. The preferred opinion is to distinguish between sale for himself (his own) and sale for the real owner. Consequently, based on the maxim “contracts follow intentions” and hadiths and other reasons the sale of the unauthorized dealer for himself (his own) is void (illegal) bur for real (original) owner is valid (legal).